Strategic communication an introduction to theory and global practice - Falkheimer, Jesper 1970-; Heide, Mats (Routledge, 2023)
"This textbook provides an overview of the core concepts, theories and methods in strategic communication, using examples from research and experiences from practice. Strategic Communication begins by explaining the fundamental concepts related to communication, organizations and strategy, and then explores the communication processes within leadership, reputation, crisis and change. The authors work to present a framework for the future, underpinned by the concept of Communicative Organizations. The content of this 2nd edition has been fully updated to incorporate the latest research and practice examples, including a new chapter on 'The Future of Strategic Communication'. The new edition also features enhanced pedagogical features to aid learning, such as key takeaways, and new international case studies and examples throughout. After reading the book the student or reader will be able to define and reflect upon strategic communication as an academic field and professional practice, describe relevant theories and apply these to communication problems. It is primarily aimed towards Advanced Undergraduate and Postgraduate students studying Strategic Communication, Corporate Communications, Public Relations and Marketing, as well as reflective practitioners looking to gain a more thorough and applied introduction to the field. Jesper Falkheimer and Mats Heide are Professors in Strategic Communication at the Department of Strategic Communication, Lund University in Sweden"--
Literaturverzeichnis: Seite 223-245
Keywords: Communication in organizations; Communication in management